Nickel phase deposition on V2CTx/V2AlC as catalyst precursors for a dry methane reforming: The effect of the deposition method on the morphology and catalytic activity. (5th April 2023) - Wysocka, Izabela; Karczewski, Jakub; Gołąbiewska, Anna; Łapiński, Marcin; Cieślik, Bartłomiej Michał; Maciejewski, Michał; Kościelska, Barbara; Rogala, Andrzej
Abstract: Dry reforming of methane (DRM) is a promising alternative technology for the production of syngas with simultaneous utilization of two main greenhouse gases (CH4, CO2 ). However, DRM technology is still an industrially immature process due to the lack of stable and active catalyst. Therefore, the search for new catalytic materials is of great research interest. Recently, MAX and MXenes materials are increasingly being tested as potential materials for catalytic processes including dry reforming of hydrocarbons. However, transition metal carbides may be deactivated under DRM conditions due to phase transition caused by an oxidation process. The combining of the MAX/MXene materials with nickel phase may be beneficial for to improve catalytic activity and stability. In this view, we report preparation and characterization of nickel-modified V2 CTx/V2 AlC materials. The Ni–V2 CTx/V2 AlC catalysts were prepared using HF-etching followed by impregnation/precipitation method. The effect of preparation route on morphology and catalytic activity was investigated. The properties of fresh and spent catalysts were evaluated using XRD, XPS, MP-AES, SEM, BET surface area, H2 -TPR, CO2 -TPD, TG/DTG and TEM techniques. Catalytic activity was investigated in the DRM process at 800 °C and 1 bar. It was found that the V2 CTx /V2 AlC- based materials undergo phase transition to vanadium oxide V2 O3, vanadium carbide V8 C7 and aluminium oxide. The presence of nickel was crucial for the catalyst activity of V2 CTx /V2 AlC- based catalysis. The catalytic activity was different and related to the preparation procedure resulting in dissimilar nickel-phase morphology and intercalation of sodium ions. It was found that the distribution of nickel phase and presence of alkali ions determined catalysts' activity and stability. The highest activity and stability in DRM process was observed for Ni–V2 CTx /V2 AlC_IMP catalysts obtained using only impregnation method without precipitation agents. For the catalysts nickel phase was distributed uniformly forming needle-like structures. The CO2 and CH4 conversions during 20 h-test were in the range of 90–93% and 90-80%, respectively. The molar ration of H2 to CO in outlet stream fluctuated from 1.05 in the first hour of the process to 0.95 after 20 h of the DRM. The activity and stability of Ni–V2 CTx /V2 AlC_IMP catalyst was higher compared to unmodified V2 CTx /V2 AlC, unetched V2 AlC and Ni–SiO2 . Highlights: The nickel phase is crucial for effective DRM over MXene/MAX materials. The method of nickel phase deposition was crucial for DRM efficiency. The Ni–V2 CTx /V2 AlC-based catalysts were tested in DRM for the first time. The Ni–V2 CTx /V2 AlC-based catalysts underwent phase change to Ni–V2 O3 –V8 C7 . The content of sodium ions retarder the activity of Ni–V2 CTx /V2 AlC-based catalysts.